Effect of chitosan coating incorporated with oregano or cinnamon essential oil on the bacterial diversity and shelf life of roast duck in modified atmosphere packaging. (September 2021) - Chen, Xue; Chen, Wenwen; Lu, Xiao; Mao, Yanwei; Luo, Xin; Liu, Guoxing; Zhu, Lixian; Zhang, Yimin
Graphical abstract: Highlights: Chitosan edible coating with oregano or cinnamon essential oil were first applied on roast duck slices. Both OEO and CEO coating effectively inhibited the bacterial growth on roast duck. Both OEO and CEO coating extended the shelf life of roast duck to >21 days. The addition of both essential oils in the coating did not change the sensory acceptance of roast duck slices. The growth of Vibrio spp. was delayed in CH-OEO and CH-CEO within the earlier period of storage. Abstract: The present study aimed to investigate the effect of chitosan edible coating containing 0.15% oregano essential oil (OEO) or 0.60% cinnamon essential oil (CEO) on the quality characteristics and dynamic changes in the bacterial community of roast duck slices under modified atmosphere packaging (MAP, 30% CO2 /70% N2 ) during 21 days of storage at 2 ± 2 °C. The results showed that the application of chitosan coating (CH) alone inhibited the growth of microorganisms and prevented lipid oxidation throughout storage. Moreover, the storage stability was further improved by including OEO or CEO, which lowered ( P  < 0.05) values for total viable count (TVC), Enterobacteriaceae, 2-thiobarbituric acid reactive substance (TBARS) and total volatile basic nitrogen (TVB-N). Based on the microbiological results, the shelf-life of CH-OEO and CH-CEO treated roast duck slices was prolonged by at least 7 days compared to that of the control. In addition, packaging types applied in this study played a major role in the bacterial community development. Notably, Vibrio spp. were the most predominant bacteria in all samples, when TVC values approached the shelf-life threshold, suggesting that this bacterium may be the main contributor to the spoilage of roast duck. The growth inhibition of Vibrio spp. in the CH-OEO and CH-CEO treatments during the early period of chilled storage might be the reason for the extension of the shelf life. Taken together, CH incorporated with OEO or CEO could be developed as prospective edible packaging materials to preserve roast duck meat.